Currents of rationalism in Western political thought - Siham Mahdi, Assistant Professor Dr. Abeer (The college of law and political science journal, 2023)
Saw Contemporary Arab Thought shifts several imposed by some WesternLQWHOOHFWXDODQGSKLORVRSKLFDOFXUUHQWVDQGLQÁXHQFHGWKHFRPSRVLWLRQDQGLGHQWLI\trends, as well as the challenges that they increasingly have to contend with andcan answer these challenges to several internal and external factors producedseveral streams addressed rationality topic in contemporary Arab thought, perhapsthe most prominent of the reformist movement, the liberal trend, mental and currentcash.